-
Notifications
You must be signed in to change notification settings - Fork 1
/
Copy patheisensten_triples.tex
295 lines (233 loc) · 11.6 KB
/
eisensten_triples.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
\documentclass{article}
\usepackage{latexsym}
\usepackage{amsmath}
\usepackage{amssymb}
\usepackage{amsthm}
\usepackage{graphicx}
\newtheorem{theorem}{Theorem}[section]
\begin{document}
\title{Eisenstein Triples: Connecting geometry and number theory}
\author{Dave Neary}
\maketitle
\section{A number theory problem}
We start with a number theory puzzle: Can you find positive integer triples $(a,b,c)$ such that:
\[ \frac{1}{a+c} + \frac{1}{b+c} = \frac{3}{a+b+c} \]
To get started with our exploration, let's clear denominators by multiplying across by
$(a+c)(b+c)(a+b+c)$ to get:
\begin{equation*}
\begin{split}
(b+c)(a+b+c) + (a+c)(a+b+c) & = 3(a+c)(b+c) \\
a^2 + b^2 + 2c^2 + 2ab + 3bc + 3ac & = 3ab + 3ac + 3bc + 3c^2 \\
a^2 - ab + b^2 &= c^2
\end{split}
\end{equation*}
Our goal will be to find positive integer solutions to this equation.
\section{A geometric aside}
This equation may look familiar to anyone who has come across the cosine rule in geometry.
For the sides of a triangle $(a,b,c)$ with opposite angles $(A,B,C)$:
\[ c^2 = a^2 + b^2 -2ab\cos(C) \]
with similar equations for $a^2, b^2$.
Rewriting the equation above in this form, we can see that the problem is equivalent to finding
triangles with integer sides $(a,b,c)$ such that $\cos(C) = \frac{1}{2}$ - that is,
$C = \frac{\pi}{3}$. In other words, our challenge is to find triangles with one angle measuring
$60^{\circ}$ which have integer side lengths.
This is a well known problem that has been explored by many number theorists in the past, and
triples of this form are known as Eisenstein triples, named after the mathematician Eisenstein.
By considering the problem as one of triangles with a certain constraint, perhaps we can approach
this problem the way we would approach finding Pythagorean triples.
\section{Factoring sums of squares}
One way to generate Pythagorean triples is to factor $a^2+b^2$ over the Gaussian integers - that is,
the subset of the complex numbers $a+ib$ with $a,b\in \mathbb{Z}$. In the Gaussian integers, we can
rewrite $ a^2 + b^2 = a^2 - b^2i^2$ as a difference of two squares - yielding a factorization:
\[ c^2 = a^2 + b^2 = (a+ib)(a-ib) \]
How does this help? Well, if we take an arbitrary Gaussian integer $z = a+ib$, the length of $z$ is
$|z| = \sqrt{a^2+b^2}$ - so if we take the length of $z^2$, we are guaranteed to get an integer
length, since $|z|^2 = |z^2|$. We will have:
\begin{equation*}
\begin{split}
z^2 &= (a+ib)^2 \\
& = a^2-b^2 + i(2ab) \\
|z^2| &= \sqrt{(a^2-b^2)^2 + (2ab)^2 }\\
|z|^2 &= a^2 + b^2 \\
|z^2| &= |z|^2 \\
\Rightarrow (a^2-b^2)^2 + (2ab)^2 &= (a^2 + b^2)^2
\end{split}
\end{equation*}
So if we take \textbf{any} positive integers $(a,b)$, we can generate a Pythagorean triple
$(a^2-b^2, 2ab, a^2+b^2)$ from them.
Can we use a similar approach with our puzzle? Indeed we can!
\section{Factoring the quadratic in $\mathbb{C}$}
We can factor $a^2 - ab + b^2$ in complex numbers too by setting it equal to zero and using
the quadratic formula:
\begin{equation*}
\begin{split}
a^2 - ab + b^2 &= 0 \\
a &= \frac{1}{2}\left(b \pm \sqrt{b^2-4b^2}\right) \\
&= \frac{b}{2}\left(1 \pm \sqrt{3}i\right)
\end{split}
\end{equation*}
The factorization is:
\[ a^2 - ab + b^2 =
\left(a + \frac{b}{2}\left(-1 - \sqrt{3}i\right) \right)
\left(a + \frac{b}{2}\left(-1 + \sqrt{3}i\right) \right) \]
If you have done any complex analysis these roots might look familiar to you. Given
$z = \frac{1}{2}(-1+\sqrt{3}i)$ then:
\begin{equation*}
\begin{split}
z^2 & = \frac{1}{4}(-1+\sqrt{3}i)^2 \\
& = \frac{1}{4}(1 - 2\sqrt{3}i - 3) \\
& = \frac{1}{2}(-1 - \sqrt{3}i) \\
& = \bar{z}
\end{split}
\end{equation*}
and:
\begin{equation*}
\begin{split}
z^3 & = \frac{1}{8}(-1+\sqrt{3}i)^3 \\
& = \frac{1}{8}(- 1 + 3\sqrt{3}i +9 -3\sqrt{3}i) \\
& = 1
\end{split}
\end{equation*}
These are the cube roots of unity, $\omega = \frac{1}{2}(-1+\sqrt{3}i), \omega^2 = \frac{1}{2}(-1-\sqrt{3}i)$.
One identity of the cube roots that we will use below is that $1 + \omega + \omega^2 = 0$, so
$\omega = -1 -\omega^2$ and $\omega^2 = -1 -\omega$.
We can rewrite our original problem expression as:
\[ c^2 = (a+\omega b)(a + \omega^2 b) \]
Let's try the same trick as we used with Pythagorean triples, and see what happens when we start with
$z = a + \omega b$ for $a,b\in \mathbb{Z}$.
\begin{equation*}
\begin{split}
|z| & = \sqrt{(a+\frac{b}{2})^2 + (\frac{\sqrt{3}b}{2})^2} \\
&= \sqrt{a^2-ab+b^2}
\end{split}
\end{equation*}
In general, $|a+ \omega b| = |a + \omega^2 b| = \sqrt{a^2-ab+b^2}$.
\begin{equation*}
\begin{split}
z^2 & = a^2 + 2ab\omega +\omega^2 b^2 \\
z^2 & = a^2 + 2ab\omega +(-1 - \omega) b^2 \\
& = (a^2 -b^2) + (2ab - b^2)\omega \\
|z^2| &= \sqrt{(a^2-b^2)^2 - (a^2-b^2)(2ab-b^2) + (2ab-b^2)^2}
\end{split}
\end{equation*}
And since $|z^2| = |z|^2$ we get:
\[ (a^2-ab+b^2)^2 = (a^2-b^2)^2 - (a^2-b^2)(2ab-b^2) + (2ab-b^2)^2 \]
So, given any positive integers $(a,b)$, we can generate triples satisfying the equation
$(a^2-b^2, 2ab-b^2, a^2-ab+b^2)$.
Trying some values we find:
\begin{equation*}
\begin{split}
(a,b) = (2,1) & \Rightarrow (a^2-b^2, 2ab-b^2, a^2-ab+b^2) = (3, 3, 3) \\
(a,b) = (3,1) & \Rightarrow (a^2-b^2, 2ab-b^2, a^2-ab+b^2) = (8, 5, 7) \\
(a,b) = (4,3) & \Rightarrow (a^2-b^2, 2ab-b^2, a^2-ab+b^2) = (7, 15, 13)
\end{split}
\end{equation*}
We can easily check that $7^2 = 8^2 - (8)(5) + 5^2$ and $13^2 = 7^2 - (7)(15) + 15^2$.
We have a formula to generate an infinite number of triples satisfying our equation $a^2-ab+b^2=c^2$ - nice!
Let's check that they also solve our initial puzzle:
\begin{equation*}
\begin{split}
\frac{1}{7+13} + \frac{1}{15+13} & = \frac{1}{20} + \frac{1}{28} \\
& = \frac{48}{560} \\
& = \frac{3}{35} \\
& = \frac{3}{7 + 13 + 15}
\end{split}
\end{equation*}
\section{A geometric approach}
Does this method yield all possible triples? It is hard to tell, but we have other tools that we can
use to find that answer. Again, we are going to start with a search for Pythagorean triples to
explore this approach.
\begin{figure}[htb]
\center{\includegraphics[width=0.9 \linewidth]{Pythagorean_circle.png}}
\caption{Finding rational points with a line of rational slope}
\label{fig:pyth_circle}
\end{figure}
Replacing $x = \frac{a}{c}, y = \frac{b}{c}$, we can see that finding integer solutions to $a^2 + b^2 = c^2$
is equivalent to finding rational solutions to $x^2 + y^2 = 1$. This is the equation of a circle of radius 1,
centered on the origin.
If we can find a way to find all rational points on the perimeter of the circle, then we will have found all
possible pythagrean triples, up to multiplication by a scalar (since if $a^2 + b^2 = c^2$, then
$(ka)^2 + (kb)^2 = (kc)^2$ for all $k \in \mathbb{Z}$). One way we can do that is to find one rational
point on the circle (say, $(0,-1)$, and draw lines through that point with a rational slope. We can show
that, since the slope of the line is rational, and the equation of the circle has integer coefficients, then
if one intersection point is rational (as it is by design), then the other point must also be rational.
Let's take an example to see how it happens. The line of slope $t$ through $(x,y) = (-1,0)$ is:
\[ y = tx +t\]
Clearly, $(-1,0)$ is on this line. Now, substituting this value of $y$ into the equation of the circle,
$x^2+y^2-1 = 0$, we get:
\[x^2 + (tx+t)^2 -1 = (1+t^2)x^2 +2t^2x + t^2 -1 = 0 \]
And solving for $x$ we get $x = -1$ or $x = \frac{1-t^2}{1+t^2}$. Substituting this value of $x$ back into
our line, we get $y = \frac{2t}{1+t^2}$. We can easily verify that for any value of $t$ that this satisfies
the equation of the circle, as expected. And since $t$ is rational, $x$ and $y$ are guaranteed to be
rational too.
Is it possible, though, that we would somehow miss rational points in the circle by this method?
No - given any rational point $(x,y)$ on the perimeter of the circle, the slope of the line through
$(x,y)$ and $(-1,0)$ is $\frac{y}{x+1}$, which is clearly rational. Since this would be a line with rational
slope which goes through the point $(-1,0)$, we are guaranteed that by enumerating all of the rational
numbers for line slopes, we are guaranteed to hit all of the rational points on the circle.
If we take the slope to be $t = \frac{m}{n}$ for $m,n \in \mathbb{Z}$ we can multiply across the
top and bottom by $n^2$ in the formulas for $x = \frac{1-t^2}{1+t^2}, y = \frac{2t}{1+t^2}$ to give
the Pythagorean triples $a = n^2-m^2, b = 2mn, c = n^2 + m^2$ for the familiar formula we found above.
Taking this approach with our problem, we substitute $x = \frac{a}{c}, y = \frac{b}{c}$ to get the equation:
\[ x^2 - xy + y^2 = 1 \]
\begin{figure}[htb]
\center{\includegraphics[width=0.9 \linewidth]{Eisenstein_ellipse.png}}
\caption{Finding rational points with a line of rational slope}
\label{fig:eisen_ellipse}
\end{figure}
This is an ellipse, centered on the origin, which goes through the points $(0,-1), (0,1), (-1,0), (1,0)$
on the X and Y axis. There are also a few other "nice" rational points on the curve at $(-1,-1), (1,1)$.
Now taking the same approach, given any rational number $t$, we can find the intersection points of our
ellipse and the line $y = t(x+1)$ (which again goes through $(-1,0)$):
\begin{equation*}
\begin{split}
x^2 - xy + y^2 & = x^2 - tx(x+1)+t^2(x+1)^2 \\
&= (1-t+t^2)x^2 +(2t^2-t)x + t^2 \\
&= 1
\end{split}
\end{equation*}
Now factoring to find the intersection points, we find, as expected, one of the points at $x=-1$, and
the other is a rational function of $t$:
\begin{equation*}
\begin{split}
(1-t+t^2)x^2 + (2t^2-t)x + (t^2-1) &= 0 \\
(x + 1)((1-t+t^2)x + (t^2 - 1)) = 0
\end{split}
\end{equation*}
So we have $x = -1$ or $x = \frac{1 - t^2}{1-t+t^2}$ for rational $t$.
Substituting the valie for $x$ back into the equation for the line:
\[ y = t(x+1) = \frac{2t - t^2}{1-t+t^2} \]
And replacing $t = \frac{m}{n}$ and multiplying through with $n^2$ above and below the line we get:
\[(x,y) = \left(\frac{n^2-m^2}{n^2-mn+m^2}, \frac{2nm - m^2}{n^2-mn+ m^2}\right) \]
And clearing a common denominator, we get an integer triple
$(a,b,c) = (n^2 - m^2, 2nm - m^2, m^2 - mn + n^2)$ as before.
A similar argument as before shows that this will find \textbf{all} rational points on the
ellipse, giving all integer solutions to the original problem (after dividing out any common factors
of $a, b, c$).
Interestingly, if we take a different rational point on the ellipse, we will get a different, but
equally valid, formula for generating Eisenstein triples from rational numbers. The equation of
a line through $(-1,-1)$, for example, is $y + 1 = t(x + 1)$. Isolating $y$, and substituting this
into the equation of the ellipse, we get:
\begin{equation*}
\begin{split}
x^2 - xy + y^2 - 1 & = x^2 - x(t(x+1)-1) + (t(x+1)-1)^2 - 1\\
& = x^2 -tx^2 -tx + x + t^2(x^2+2x+1)-2t(x+1)+1 \\
& = (1 - t + t^2)x^2 + (1 - 3t + 2t^2)x + (t^2-2t) \\
& = (x+1)((1 - t + t^2)x + (t^2-2t)) = 0
\end{split}
\end{equation*}
Giving the solutions $x = -1$ or $x = \frac{2t-t^2}{1-t+t^2}$.
Substituting this back into the equation for the line, we get:
\begin{equation*}
\begin{split}
y &= t\left(\frac{2t-t^2}{1-t+t^2} + 1\right) - 1 \\
& = \frac{t^2 + t}{1-t+t^2} - 1 \\
& = \frac{2t - 1}{1 - t + t^2}
\end{split}
\end{equation*}
Replacing $t = \frac{m}{n}$, we get:
\[ x = \frac{2mn - m^2}{m^2 - mn + n^2}, y = \frac{2mn - n^2}{m^2 - mn + n^2} \]
Which gives an alternative form for triples of:
\[ (a,b,c) = (2mn - m^2, 2mn - n^2, m^2 -mn + n^2) \]
which, surprisingly perhaps, is exactly equivalent to the formula we found earlier.
\end{document}